Some Steps in Shrimp Nutrition «a linear way» - G., Cuzon; G., Gaxiola (Facultad de Ciencias Biologicas, 2010)
In the early 70‟s, applied research was proposed to support pilot stage of penaeid shrimp farming. Later, some nutritional requirements could be addressed with an increased demand for a grower feed through a study on recommended Protein/Energy ratios for P. vannamei and P. stylirostris. The work on squid factor gave an indication on a growth factor. Many attempts to mimic Nippai feed led shrimp mature under captive conditions. COP was pioneering on molt stages and its application to penaeid. The IWGCN was an opportunity to exchange information with the industry on ingredients such as wheat or amino acids, vitamins, fatty acids, growth factor. Feed technology and formulation contributed to feed texture, presentation, and stability in sea water. Shrimp in earthen ponds receive natural productivity as part of their food intake, and techniques with stable isotopes gave values on respective contribution of feed and meiofauna. “Floc”, investigated in the early 80‟s, was another option to promote weight gain at high stocking density, the shrimp being surrounded by kind of an external rumen. Recently breeders maintained in “floc” tanks have spawned 6 times per female/month while females from earthen ponds gave 2spawns/female/month. Immune response via β-glucans was tested. Recently, nutrigenomics dealt with digestive enzymes gene expression in early stages and on juveniles. A collaborative work on several species was dedicated to replace fish meal with plant-based protein. These lines of research coupled with bioenergetics will contribute to minimize wastes.